2008
DOI: 10.1016/j.mce.2008.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Role of TRPV1 receptors in descending modulation of pain

Abstract: Transient receptor potential vanilloid type 1 (TRPV1) receptor is a ligand-gated non selective cation channel activated by heat (>43°), low pH and endogenous lipid molecules such as anandamide, Narachydonoyl-dopamine, N-acyl-dopamines and products of lipoxygenases (12-and 15-(S)-HPETE) termed endovanilloids. Apart from peripheral primary afferent neurons and dorsal root ganglia, TRPV1 receptor is expressed throughout the brain. Recent evidence show that TRPV1 receptor stimulation by endocannabinoids or by caps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 48 publications
2
57
0
4
Order By: Relevance
“…7) Given that TRPV1 is expressed in peripheral and central terminals of non-myelinated primary afferent neurons, and also in various brain regions, 2,12) our results suggest that AS1928370 should act on TRPV1 in these tissues.…”
Section: Discussionmentioning
confidence: 77%
“…7) Given that TRPV1 is expressed in peripheral and central terminals of non-myelinated primary afferent neurons, and also in various brain regions, 2,12) our results suggest that AS1928370 should act on TRPV1 in these tissues.…”
Section: Discussionmentioning
confidence: 77%
“…98 Spinal cells projecting in the spino-RVM pathway predominate in laminae V, VII, VIII and X, whereas neurons of origin of the spino-PAG pathway are located in laminae I, IV-V, VI-VIII and the lateral spinal nucleus. 98 Furthermore, 'OFF'-RVM neurons mainly express NMDA/AMPA 69 and TRPV1 99 receptors. Under physiological conditions, PAG neurons release glutamate over 'OFF'-RVM neurons, causing their depolarization via NMDA/AMPA receptors.…”
Section: Molecular Neuroplasticity Of the Descending Inhibitory Pain mentioning
confidence: 99%
“…Descending projections from PAG reach the rostral ventromedial medulla (RVM) and the activation of PAG-RVM pathway leads to a decrease in the perception of pain [26][27][28]. Initial studies conducted by Palazzo and colleagues concerning the putative role of TRPV1 channels within PAG-RVM descending nociceptive pathway showed that microinjection of capsaicin, a TRPV1 agonist, into the dorsal portion of the PAG (dPAG) increased the latency of nociceptive response in rats subjected to the plantar test, an acute nociceptive test [1].…”
Section: Introductionmentioning
confidence: 99%